2020
DOI: 10.2337/dc19-1745
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Liraglutide 3.0 mg in Individuals With Overweight or Obesity and Type 2 Diabetes Treated With Basal Insulin: The SCALE Insulin Randomized Controlled Trial

Abstract: Most individuals with type 2 diabetes also have obesity, and treatment with some diabetes medications, including insulin, can cause further weight gain. No approved chronic weight management medications have been prospectively investigated in individuals with overweight or obesity and insulin-treated type 2 diabetes. The primary objective of this study was to assess the effect of liraglutide 3.0 mg versus placebo on weight loss in this population. RESEARCH DESIGN AND METHODS Satiety and Clinical AdipositydLira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 25 publications
2
106
0
11
Order By: Relevance
“…35,36 Moreover, the distribution of body fat loss in patients treated with bimagrumab was highly favorable, with reduction of abdominal visceral adipose tissue and waist circumference that was nearly twice that observed in a recently published study of patients with type 2 diabetes treated with an intensive lifestyle program and the glucagon-like peptide 1 agonist liraglutide. 37 These observations highlight the importance of moving away from body weight as a primary efficacy marker of drugs to more metabolically relevant end points, such as total body FM.…”
Section: Jama Network Open | Nutrition Obesity and Exercisementioning
confidence: 99%
“…35,36 Moreover, the distribution of body fat loss in patients treated with bimagrumab was highly favorable, with reduction of abdominal visceral adipose tissue and waist circumference that was nearly twice that observed in a recently published study of patients with type 2 diabetes treated with an intensive lifestyle program and the glucagon-like peptide 1 agonist liraglutide. 37 These observations highlight the importance of moving away from body weight as a primary efficacy marker of drugs to more metabolically relevant end points, such as total body FM.…”
Section: Jama Network Open | Nutrition Obesity and Exercisementioning
confidence: 99%
“…While estimands do not solve all problems of trial design and interpretation, this new concept will enable trials to be designed more appropriately to obtain relevant information to address the clinical question(s) of interest. The SCALE phase 3b clinical trials have been reported [ 7 , 8 ], building on the existing evidence for the efficacy and safety of liraglutide 3.0 mg in weight management, and are some of the first clinical trials in weight management to report results using estimands.…”
Section: Reporting Results From Weight Management Clinical Trials: Moving Forwardmentioning
confidence: 99%
“…In the recent SCALE Intensive Behavioral Therapy phase 3b trial, participants were encouraged to attend scheduled visits and thus have their weight measurements recorded regardless of discontinuing treatment [ 8 ]. To promote participant retention, the SCALE Insulin phase 3b trial permitted individuals to stop and restart liraglutide 3.0 mg without re-escalating the dose, or with re-escalation if three consecutive doses had been missed [ 7 ].…”
Section: Missing Data In Weight Management Trialsmentioning
confidence: 99%
See 2 more Smart Citations